2012
DOI: 10.1071/py11014
|View full text |Cite
|
Sign up to set email alerts
|

Dementia information for culturally and linguistically diverse communities: sources, access and considerations for effective practice

Abstract: Providing information about dementia has been shown to produce immense benefits for people living with dementia and their carers. The dementia information needs of culturally and linguistically diverse (CALD) families have not been comprehensively investigated. Addressing this research gap, the current study examines the perspectives of a range of stakeholders - CALD family caregivers (Arabic, Chinese, Italian and Spanish speaking), bilingual and bicultural workers, bilingual general practitioners and geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…The third and final key finding suggests that caregivers of CALD patients prefer interpersonal sources of information (eg, health‐care providers). Existing research among CALD communities supports this preference, which has been attributed to the perception that information received from knowledgeable, professional, trustworthy and respected individuals is of high value . Few caregivers in this study described the Internet as a preferred medium for information for reasons reported by other studies, including concerns about reliability .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The third and final key finding suggests that caregivers of CALD patients prefer interpersonal sources of information (eg, health‐care providers). Existing research among CALD communities supports this preference, which has been attributed to the perception that information received from knowledgeable, professional, trustworthy and respected individuals is of high value . Few caregivers in this study described the Internet as a preferred medium for information for reasons reported by other studies, including concerns about reliability .…”
Section: Discussionmentioning
confidence: 57%
“…Existing research among CALD communities supports this preference, which has been attributed to the perception that information received from knowledgeable, professional, trustworthy and respected individuals is of high value . Few caregivers in this study described the Internet as a preferred medium for information for reasons reported by other studies, including concerns about reliability . As such, the role of information gatekeeper among caregivers of CALD patients may facilitate access to their preferred interpersonal sources, thus limiting their need to access print‐ and technology‐based sources.…”
Section: Discussionmentioning
confidence: 68%
“…This could include consumer information regarding AT and where to purchase it, which may be particularly relevant where a local authority is not able to provide for a particular individual [11,17]. Such information regarding private AT is reported to be in short supply -which is a potential barrier to any consumer market, if the potential customers are unsure of where to purchase such products [2,3,15,16] [6, p.81] However, it has been recognised that currently health and social care professionals themselves are not always aware of services pertaining to their patient's needs [10,18,19] therefore the information needs of clinicians must also be considered. As well as availability of information, the type, source, accessibility, and quality of information needs to be considered -information which is available yet inaccessible does nothing to reduce barriers to AT uptake.…”
Section: Lack Of Access To Information Regarding Atmentioning
confidence: 99%
“…Older people and disabled people (and their carers) report that information regarding long term health conditions needs to be available either via central resources, or places often frequented (such as GP waiting rooms), rather than just being available via the internet [10,11]. Indeed, for younger and older people with disabilities, access to information regarding AT is vital, as it has the potential to inform and empower people to make decisions which may improve their quality of life [12].…”
Section: Lack Of Access To Information Regarding Atmentioning
confidence: 99%
See 1 more Smart Citation